Characterization and In Vivo Evaluation of Durian Peel Extract Nanoliposome Transdermal Patch on Wound Healing - Susanto, Nindita Clourisa Amaris; Putri, Milkazia Elda; Utami, Dayinta Tyas; Ermawati, Dian Eka; Sasongko , Heru; Rohmani , Sholichah; Artanti, Anif Nur; Utami, Dyah Tri; Zulpadly Mh, M. Fiqri; Darojati, Ulfa Afrinurfadhilah; Meitasari , Annisa Diyan; Untari, Meta Kartika; Izza, Alfina (Chempublish Journal, 2026)
Wounds are a form of continuity damage due to loss of tissue, structure and anatomical function of the skin caused by heat trauma or sharp object scratches. The prevalence of wound injury patients in Indonesia is 9.2%. One of the natural ingredients that is effective in inhibiting the growth of infectious organisms is durian, especially in its skin. In this study, durian peel was formulated in liposome dosage form and applied to patch preparations. The purpose of this study was to assess the effectiveness of durian skin extract liposomes (Durio zibethinus Murr.) on wound healing in white rats. The results of this study are that the patches produced can provide a therapeutic effect on the healing of incision wounds in wistar strain male white rats (Rattus norvegicus L.) with a healing percentage on day 7 of 72.5% which is characterized by the absence of edema, bleeding, growth of fur in mice, the appearance of scabs and wound closure.